Lysimeter for evapotranspiration measurement in pepper culture in hydroponic system with substrate - De Carvalho, Renata Da Silva Cuba [UNESP]; Mota, Flávia Diniz [UNESP]; Gabriel Filho, Luís Roberto Almeida [UNESP]; Klar, Antonio Evaldo [UNESP]; Grassi Filho, Hélio [UNESP] (Brazilian Journal of Irrigation and Drainage - IRRIGA, 2020)
The purpose of this project is to evaluate the vegetative, physiological and productive development of pepper crop cultivated in a constant water table lysimeter device, due to the necessity of a crop irrigation management method in a protected environment and utilizing substrate to measure the daily consumption of water and to compare with the data estimates of crop evapotranspiration. The experiment was composed of three lysimeters of constant water table, installed inside a protected environment. One pepper plant was grown in each lysimeter in a 15 L volumetric polyethylene vessel filled with coconut husk fiber substrate, and the daily volume of nutrient solution consumed by the plants was considered to be the evapotranspiration of the crop. The cultivation was evaluated from morphological, physiological and productive measurements. The productivity obtained was 3.9 kg per plant, with total water consumption of 905 mm and water use efficiency 43.8 kg ha-1 mm-1. The constant water table lysimeters provided satisfactory development for the pepper crop from the technical point of view relatively to the vegetative, physiological and productive development and it can be used to measure crop evapotranspiration.
Lisímetro para medida da evapotranspiração na cultura do pimentão em sistema
Keywords: Capillarity; Coconut fiber; Nutrient solution; Transpiration; Vegetable